Earth-to-air heat exchanger system simulation study for IIUM Gombak - Ahmed, Soran Hama Aziz (Kulliyyah of Architectural and Environmental Design, International Islamic University Malaysia, 2013)
This study elucidates the usage of the Earth-to-Air Heat Exchanger (EAHE) system. The emphasis is on replacing the conventional air conditioning systems with the EAHE technology, as low energy cooling system for residential and commercial buildings in Malaysia. The turnover in the usage will contribute to reducing electric-energy consumption and minimize environmental impact caused by the high usage of electrical appliances for cooling in the buildings. The EAHE technology uses simple methods of transferring the air from its intake into the ground through a pipe, and it releases the air from its outlet into a building or a room. The air travels through the pipe and gives away some heat to the surrounding underground soil, and then enters into the room as cool air. To fulfill the requirements of the empirical investigations, this research utilized the EnergyPlus program to simulate the EAHE system, based on ASHRAE weather database and data collected in previous field studies at the IIUM Gombak Campus, Kuala Lumpur, Malaysia. This study went through some meta-analysis and observations on the cooling potential (ΔT) which represents the difference between ambient air temperature (Tam) and pipe outlet air temperature (Tpo). The research also observed the influence of other factors such as pipe diameter, air velocity, pipe-depth, and pipe-length on the cooling potential (ΔT). The simulation results showed that, the maximum (ΔT) achieved by utilizing the EAHE was 3.57 °C at 2:00 pm. The PVC pipe is required to achieve the aforementioned reduction of 0.075 m (3 inches) in diameter, 50 m long, and placed 1.0 m deep underground, with an air velocity of 1 m.s-1.